LncRNA TUG1 alleviates sepsis-induced acute lung injury by targeting miR-34b-5p/GAB1 - Qiu, Nan; Xu, Xinmei; He, Yingying (BMC pulmonary medicine, 2020)
Sepsis-induced acute lung injury (ALI) is a clinical syndrome characterized by the injury of alveolar epithelium and pulmonary endothelial cells. This study aimed to investigate the regulation of long noncoding RNA (lncRNA) taurine up-regulated gene 1 (TUG1) in a murine ALI model and in primary murine pulmonary microvascular endothelial cells (PMVECs) stimulated with lipopolysaccharide (LPS). Adult C57BL/6 mice were intravenously injected with or without TUG1-expressiong adenoviral vector or control vector 1 week before the establishment of ALI model. PMVECs were transfected with TUG1-expressiong or control vectors followed by LPS stimulation. MiR-34b-5p was confirmed as a target of TUG1 using dual-luciferase reporter assay. GRB2 associated binding protein 1 (GAB1) was confirmed as a downstream target of miR-34b-5p using the same method. In the rescue experiment, PMVECs were co-transfected with TUG1-expressing vector and miR-34b-5p mimics (or control mimics) 24 h before LPS treatment. ALI mice showed reduced levels of TUG1, pulmonary injury, and induced apoptosis and inflammation compared to the control group. The overexpression of TUG1 in ALI mice ameliorated sepsis-induced pulmonary injury, apoptosis and inflammation. TUG1 also showed protective effect in LPS-treated PMVECs. The expression of MiR-34b-5p was negatively correlated with the level of TUG1. TUG1-supressed apoptosis and inflammation in LPS-stimulated PMVECs were restored by miR-34b-5p overexpression. GAB1 was inversely regulated by miR-34b-5p but was positively correlated with TUG1 expression. TUG1 alleviated sepsis-induced inflammation and apoptosis via targeting miR-34b-5p and GAB1. These findings suggested that TUG1 might be served as a therapeutic potential for the treatment of sepsis-induced ALI.